2000
DOI: 10.2105/ajph.90.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Improved birth outcomes among HIV-infected women with enhanced Medicaid prenatal care

Abstract: Objectives. This study evaluated the impact of enhanced prenatal care on the birth outcomes of HIV-infected women.Methods. Medicaid claims files linked to vital statistics were analyzed for 1723 HIV-infected women delivering a live-born singleton from January 1993 to October 1995. Prenatal care program visits were indicated by rate codes. Logistic models controlling for demographic, substance use, and health care variables were used to assess the program's effect on preterm birth (less than 37 weeks) and low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…We speculate that our findings are related to a series of inter-related social and structural barriers to care for women living with HIV during the preconception and prenatal periods. This reasoning is supported by earlier literature documenting stigma, discrimination, difficulty for newcomers navigating a foreign health care system and lack of preconception counselling for women living with HIV, each of which may act as components in one or more causal mechanisms that culminate in the outcome of inadequate prenatal care [ 17 27 ].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…We speculate that our findings are related to a series of inter-related social and structural barriers to care for women living with HIV during the preconception and prenatal periods. This reasoning is supported by earlier literature documenting stigma, discrimination, difficulty for newcomers navigating a foreign health care system and lack of preconception counselling for women living with HIV, each of which may act as components in one or more causal mechanisms that culminate in the outcome of inadequate prenatal care [ 17 27 ].…”
Section: Discussionmentioning
confidence: 79%
“…However, substantial non-infectious neonatal morbidity exists in the context of HIV infection in Ontario, with risks of low birth weight, preterm birth and small for gestational age births among women with HIV exceeding those of non-infected women by 90 %, 76 % and 43 %, respectively [ 43 ]. Because research has shown that improving access to prenatal care is associated with reduced risks of these adverse neonatal outcomes in women with HIV [ 27 ], it is important to ensure that additional data are gathered from these women which inform the development of interventions that promote timely linkage to and retention in prenatal care. This may be especially salient for those women originally from Africa and the Caribbean.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Cameroon, the national HIV prevalence in 2011 was 5.6% in women and 2.9% in men, but the prevalence of HIV among pregnant women was 7.8% [3,4]. Maternal HIV-1 infection increases the risk of pre-term birth (<37 weeks of gestation), small-for-gestational age babies, and fetal intrauterine growth restriction [59], resulting in low birth weight (LBW) infants (<2500g) [1012]. Low birth weight occurs in over 20 million children and 95% of this condition is observed in developing countries [13,14].…”
Section: Introductionmentioning
confidence: 99%
“… NOTE: HAART, highly-active antiretroviral therapy; DOT, directly observed therapy; QALE, quality-adjusted life expectancy.* Complete response considered to be a sustained reduction in viral load of 2.0 log 10 copies/ml; partial response considered to be a sustained reduction of 0.75 log 10 copies/ml; non-response associated with a reduction of 0.25 log 10 copies/ml [32].† Non-elective Caesarean at term and Caesarean section with premature delivery were not associated with reduced risk of mother-to-child HIV transmission [59].‡ Base-case probability of prematurity approximates that seen in a cohort of HIV-infected New York Medicaid recipients; upper bound based on rates of premature delivery seen in a subgroup of women receiving methadone maintenance therapy [58].§ In base case, risk of antiretroviral toxicity in infants was assumed to be negligible, consistent with available data [6], [62], [65]. Risk of severe toxicity used in sensitivity analysis based on upper bound confidence limit for mitochondrial toxicity in a French cohort study [63], [64].…”
Section: Methodsmentioning
confidence: 99%